(untitled) (Italian Journal of Public Health, 2009)
Background: Few of the studies that have evaluated the impact of income on health and health services utilisation have been conducted in southern Europe and have focused on the shape of the relationship. This study aimed at evaluating the hospitalisation gradient by small area income and to analyse its shape, with data from four large Italian cities. Methods: Census tract (median 260 residents) median per capita income was computed through record linkage between 1998 national tax and local population registries in the cities of Rome, Turin, Milan and Bologna (total population of approximately 5.5 million). Census tract median income was assigned to general acute hospital discharges in the period 1997-2000 among residents in the cities, on the basis of the patient’s residence. Within each stratum defined by gender and age group (0-64, 65+), standardised hospital discharge rates were computed for quantiles of census tract median income. A segmented non-linear model was fitted to discharge rates across percentiles, as function of median value of census tract median income in each percentile. Results: This study showed an inverse gradient in hospitalizations with increasing small area income. A less marked decrease in the standardised discharge rates was shown above approximately €12,000 census tract median per capita income, for both males and females and for the two age-groups considered. Conclusions: Small area income seems to have a strong association with hospitalisation, acting through a differential occurrence of diseases and/or access to health services. Among the wealthiest persons, the results suggest the diminishing return of health and/or appropriateness of health care with increasing income.